2016
DOI: 10.1111/jmp.12220
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing alopecia and hair cortisol in rhesus macaques (Macaca mulatta)

Abstract: Background Alopecia can occur in captive nonhuman primates, but its etiology is poorly understood. The purpose of this study was to assess alopecia and hair cortisol in rhesus monkeys and to identify potential risk factors. Methods Subjects were 117 rhesus monkeys at two National Primate Research Centers. Photographs and hair samples were obtained during routine physicals. Photographs were analyzed using Image J software to calculate hair loss, and hair samples were assayed for cortisol. Results Age, days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 29 publications
2
52
0
Order By: Relevance
“…In contrast, there was no association between hair loss and hair cortisol in any of the female groups; hair loss appeared to be independent of hair cortisol. Although some studies have reported a relationship between hair loss and hair cortisol in macaque monkeys, this has not been the case in all studies or at all facilities and may be due, in part, to the severity of alopecia at a given facility.33 Upon further evaluation of the photographs in the present study, only four animals exhibited what would be considered severe alopecia (>50% of the body affected). Because the association between hair loss and stress is not consistent across facilities, alopecia may not be a reliable indicator of welfare.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In contrast, there was no association between hair loss and hair cortisol in any of the female groups; hair loss appeared to be independent of hair cortisol. Although some studies have reported a relationship between hair loss and hair cortisol in macaque monkeys, this has not been the case in all studies or at all facilities and may be due, in part, to the severity of alopecia at a given facility.33 Upon further evaluation of the photographs in the present study, only four animals exhibited what would be considered severe alopecia (>50% of the body affected). Because the association between hair loss and stress is not consistent across facilities, alopecia may not be a reliable indicator of welfare.…”
Section: Discussionmentioning
confidence: 61%
“…A comparison of three non‐human primate research facilities yielded different findings. Although a significant relationship was detected between hair loss and hair cortisol across the entire sample, this effect was driven by one facility which had a large number of monkeys with more extreme forms of hair loss …”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Alopecia, a common condition in captive non‐human primates, can affect as much as 50% or more of the hair coat . There are many possible causes of hair loss, including seasonality, age, hormonal imbalances, and friction .…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have directly focused on this particular behavior. Hair plucking has been most studied in laboratory‐housed Rhesus macaques ( Macaca mulatta ) (e.g., Reinhardt et al, ; Lutz et al, ). The behavior is both social and self‐directed and suggested to be stress‐induced.…”
Section: Introductionmentioning
confidence: 99%